Adapting Social Networking Sites for Scholarly Communication among Postgraduate Students in Kenyan Universities - Kipruto, Martha; Kitetu, Catherine; Ongus, Raymond (Journal of Information and Knowledge, 2021)
The study examines how postgraduate students use Social Networking Sites (SNS) in communicating scholarly information in Kenyan universities with reference to use of WhatsApp, Twitter, Facebook, LinkedIn and Academia.edu. The objectives of this studies are: to determine how social networking sites are used for scholarly communication and to find out the reasons for using social networking sites by postgraduate students. Descriptive research design was used to guide the study. From four universities with a sample size of 242 postgraduate students who filled the questionnaire. The findings of the study showed that postgraduate students use SNS to share research ideas, class experiences, to know where to meet for lessons, when lectures are starting and updates on deadlines for submitting class assignments; the reasons for using SNS are for academic purposes and group discussion. In conclusion, the findings of the study show that postgraduate students use SNS to share daily experiences within campus rather than sharing information on how and where they can get scholarly information that will enable them to add new body of knowledge.